(3GdJGL Gdecdd HLhGgQ GdBOGH Ydi cJGH GdeaUd aj UfYI GdEYQGHs - (3LeGd GdOjf Ydj Hf eMeO Hf SdjeGf GdeYQha LOg HgWHds; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3eMeO Hf YHO GdQMef Hf YHO Gddg GdMSf GdCSOi GdMGQKi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg GdJi dG JMU hHYO aEfg deG cGf Yde GdYQHjI ef CfaY GdYdhe hCgOGgG Edi eYQaI cdGe GdMi Gdbjhe s
(3BNQgG (B:s
(3hdhdG Pdc dcGf GdMPa ajeG JYPQ ajg GdEOZGe HGYJHGQ TPhPjgeG hGddg CYde bGd GdeDda gPG BNQ GdTQM HGdeHGQc Ydi cJGH GdeaUd s
(3HChdg GdYOjO ef GdJedcGJs
(3cJHJ HNW bdjd GdfbW bOjes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs